2019
DOI: 10.1017/s0007114519001119
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of results from genome-wide association studies of micronutrient status and their utility in the practice of precision nutrition

Abstract: Rapid advances in ‘omics’ technologies have paved the way forward to an era where more ‘precise’ approaches – ‘precision’ nutrition – which leverage data on genetic variability alongside the traditional indices, have been put forth as the state-of-the-art solution to redress the effects of malnutrition across the life course. We purport that this inference is premature and that it is imperative to first review and critique the existing evidence from large-scale epidemiological findings. We set out to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…The ability to identify a person having genetic variants involved in vitamin and mineral metabolism may reduce the chance of developing micronutrient deficiencies that can lead to various diseases [19]. GWAS have shown that several genetic variants associated with vitamin metabolism can affect circulating vitamin levels, which could lead to abnormal vitamin function [24]. Most GWAS have been conducted among healthy, Caucasian populations, which is a limitation in this research [24].…”
Section: Genetic Variants and Their Effect On Vitamin And Mineral Patmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to identify a person having genetic variants involved in vitamin and mineral metabolism may reduce the chance of developing micronutrient deficiencies that can lead to various diseases [19]. GWAS have shown that several genetic variants associated with vitamin metabolism can affect circulating vitamin levels, which could lead to abnormal vitamin function [24]. Most GWAS have been conducted among healthy, Caucasian populations, which is a limitation in this research [24].…”
Section: Genetic Variants and Their Effect On Vitamin And Mineral Patmentioning
confidence: 99%
“…GWAS have shown that several genetic variants associated with vitamin metabolism can affect circulating vitamin levels, which could lead to abnormal vitamin function [24]. Most GWAS have been conducted among healthy, Caucasian populations, which is a limitation in this research [24]. Table 1 demonstrates recent studies that associate genetic variants and micronutrient metabolism.…”
Section: Genetic Variants and Their Effect On Vitamin And Mineral Patmentioning
confidence: 99%
“…More common effects of genetic variation in B 12 levels can be described by its heritability (h 2 ) in different populations as well as associations between specific polymorphisms in genes and the various indicators of B 12 status. Dib et al [65] have provided robust h 2 estimates for all markers of vitamin B 12 status for UK-based Caucasian populations that range from $15% in the case of MMA right up to $80% for holoTC, highlighting that B 12 status is a complex and multifactorial trait, whereby several polymorphisms in multiple genes interact with the environment to cause variable B 12 status. So far, candidate gene and genomewide association studies (GWAS) have identified $59 SNPs from 19 genes involved in cobalamin metabolism and various indicators of its status [66].…”
Section: Genetic Polymorphisms Associated With Poor B 12 Statusmentioning
confidence: 99%
“…Related to nutrition status, and equally suspect in terms of predictive validity, is personalised nutrition advice from multiple companies claiming to help consumers maintain healthy levels of vitamins, antioxidants and minerals, on the basis of a handful of genetic variants. In contrast to obesity and type 2 diabetes, to date much fewer loci have been associated with the biomarkers of micronutrient status (60) . These explain only a small fraction of variance in micronutrient status.…”
Section: Personalised Nutrition and Consumer Genomicsmentioning
confidence: 99%
“…Notably, while scientists have remained largely circumspect about clinical utility and the extent to which genetic or polygenic risk scores can explain overall risk for common, multifactorial diseases (e.g. obesity, diabetes, fatty liver) or micronutrient status (59,60) ; an astonishing number of direct-to-consumer (DTC) genetic testing companies have proliferated offering personalised nutrition advice to individuals based on nutrigenetic testing via the Internet (61) .
Fig.
…”
Section: Personalised Nutrition and Consumer Genomicsmentioning
confidence: 99%